Sumoylation regulates the stability and nuclease activity of Saccharomyces cerevisiae Dna2 - Ranjha, Lepakshi; Levikova, Maryna; Altmannova, Veronika; Krejci, Lumir; Cejka, Petr (Communications biology, 2019)
Dna2 is an essential nuclease-helicase that acts in several distinct DNA metabolic pathways including DNA replication and recombination. To balance these functions and prevent unscheduled DNA degradation, Dna2 activities must be regulated. Here we show that Saccharomyces cerevisiae Dna2 function is controlled by sumoylation. We map the sumoylation sites to the N-terminal regulatory domain of Dna2 and show that in vitro sumoylation of recombinant Dna2 impairs its nuclease but not helicase activity. In cells, the total levels of the non-sumoylatable Dna2 variant are elevated. However, non-sumoylatable Dna2 shows impaired nuclear localization and reduced recruitment to foci upon DNA damage. Non-sumoylatable Dna2 reduces the rate of DNA end resection, as well as impedes cell growth and cell cycle progression through S phase. Taken together, these findings show that in addition to Dna2 phosphorylation described previously, Dna2 sumoylation is required for the homeostasis of the Dna2 protein function to promote genome stability.
Keywords: Saccharomyces cerevisiae Proteins; poškození DNA; Recombinant Fusion Proteins; DNA, Fungal; Enzyme Stability; DNA Damage; fosforylace; Saccharomyces cerevisiae; Phosphorylation; Sumoylation; sumoylace; rekombinantní fúzní proteiny; DNA fungální; proteinové domény; stabilita enzymů; kinetika; DNA Helicases; DNA-helikasy; metabolické sítě a dráhy; Saccharomyces cerevisiae - proteiny; replikace DNA; DNA; DNA Replication; Genomic instability; Protein Domains; Metabolic Networks and Pathways; Kinetics